Code-Switching Used In Judges’ Utterances of Masterchef Indonesia Season 7 Grand Final Episodes - Mac Aditiawarman; Kinara Vidolantia (Fakultas Sastra Universitas Ekasakti, 2022)
This study deals with the types and functions of code switching used in the speeches of the judges of MasterChef Indonesia Season 7 at the grand final episode,in line with that this research also analyzed the social aspects that affected code switching based on these utterances. The judges of MasterChef Indonesia Season 7 who had educational backgrounds abroad made them accustomed to using code switching in their speech. The aim of this research are (1) To analyze the types of code-switching used in judges’ utterances of MasterChef Indonesia Season 7 grand final episodes, (2) To analyze the functions of code-switching used in judges’ utterances of asterChef Indonesia Season 7 grand final episodes. The data source of this research was obtained by watching and listening to 12 video CDs from an online video sharing platform called YouTube. The researchers find three types of code-switching: 7 tag switching, 53 inter-sentential switching, and 17 intra-sentential switching. The functions of code-switching found in this research are only four functions, they are 25 referential functions, 8 directive functions, 28 expressive functions, and 6 phatic functions. The social aspect affecting code-switching in this research is social class and status.